Community Participation in Solid Waste Management “Learn From International Best Practices” - Acwin Dwijendra, Ngakan Ketut (Bumi Lestari; Vol 7 No 2)
In most cities of many developing countries, solid waste management is constantly growing to be a great issue. This is due to the rise of waste, while the city authorities has lack of finance and technical skills in collecting and disposing it effectively. The solid waste problem is nott just been responsibling of the city council but also other parties. This article reviews international cases of solid waste management programs analyses and evaluate each cases based on some selected criteria and then trs to check the possibility to apply in Denpasar City condition. The cases show that by enhancing and encouraging the involvement of community is one of the best way to set up a successful to sustainabile solid waste management programs.
Keywords: community participation, solid waste management, international best practices.